Inactivation of norovirus surrogates by kimchi fermentation in the presence of black raspberry. (September 2018) - Bae, Garam; Kim, Jeongwon; Kim, Hyojin; Seok, Jong Hyeon; Lee, Dan Bi; Kim, Kyung Hyun; Chung, Mi Sook
Abstract: Kimchi, a food made of seasoned vegetables is probiotic-rich when fermented. Recent increases in the consumption of commercially-made kimchi have resulted in norovirus outbreaks in schools where freshly-prepared kimchi is served. We previously showed that black raspberry ( Rubus coreanus ) seed extract (RCS), inactivated murine norovirus (MNV) and feline calicivirus (FCV). The aim of this study was to evaluate the antiviral effects of RCS on MNV and FCV in kimchi fermentation for 50 days, during which fresh baechu kimchi became optimally ripened and acidic (∼pH 4.3). During the fermentation period, recovered FCV titers were significantly reduced by 1.7 log PFU/ml at day 0, to undetectable levels at day 30, primarily due to the effects of RCS and the acidic pH produced by lactic acid bacteria. In contrast, recovered MNV titers were reduced by 1.1 and 2.1 log PFU/ml at days 0 and 50, respectively, by kimchi seasonings with RCS. Two seasoning ingredients, red pepper and garlic, showed significant antiviral effects on MNV, and their major components, capsaicin and alliin at 10–200 μM, inhibited MNV in a concentration-dependent manner. Optimally ripened kimchi in the presence of RCS can thus provide the potential to reduce norovirus outbreaks in catering service settings. Highlights: Inactivation of norovirus surrogates by kimchi fermentation in the presence of RCS. RCS showed an immediate antiviral effect on FCV at the onset of fermentation. FCV was inhibited significantly by acidic pH produced by lactic acid bacteria. MNV was inhibited significantly by kimchi seasonings, red pepper and garlic. Alliin and capsaicin inhibited MNV in a dose-dependent manner.